Convergent evolution of niche structure in Northeast Pacific kelp forests. (23rd July 2020) - Starko, Samuel; Demes, Kyle W.; Neufeld, Christopher J.; Martone, Patrick T.
Abstract: Much of the morphological and ecological diversity present on earth is believed to have arisen through the process of adaptive radiation. Yet, this is seemingly at odds with substantial evidence that niches tend to be similar among closely related species (i.e. niche conservatism). Identifying the relative importance of these opposing processes in driving niche evolution under different circumstances is therefore essential to our understanding of the interaction between ecological and evolutionary phenomena. In this study, we make use of recent advances in our understanding of the phylogeny of kelps (Laminariales) to investigate niche evolution in one of the most ecologically significant groups of benthic habitat‐forming organisms on the planet. We quantify functional traits and use community sampling data from a kelp diversity hotspot to determine which traits are responsible for the habitat (β) niche of kelps and whether they are labile or conserved across the kelp phylogeny. We find that combinations of functional traits have evolved convergently across kelp subclades and that these functional traits are significant predictors of community structure. Specifically, traits associated with whole‐kelp structural reinforcement and material properties were found to be significantly correlated with species distributions along a gradient of wave disturbance and thus predict the outcome of environmental filtering. However, kelp assemblages were made up of species that are more phylogenetically distinct than expected (i.e. phylogenetic overdispersion), suggesting that niche partitioning along this gradient of wave disturbance has been an important driver of divergence between close relatives. These results are consistent with the hypothesis that environmental filtering associated with wave disturbance plays an essential role in determining the habitat niche of kelps across local communities and further suggest that this process can drive phenotypic divergence and niche partitioning between close relatives. We propose that parallel adaptive radiation of kelp subclades has shaped the diversity and species composition of kelp forests in the Northeast Pacific and we discuss how evidence from the literature on incipient or ongoing speciation events supports this hypothesis. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.